2020
DOI: 10.1111/lsq.12273
|View full text |Cite
|
Sign up to set email alerts
|

Coalition Prospects and Policy Change: An Application to the Environment

Abstract: In most developed democracies, parties adjust their positions to polls and public opinion. Yet, in a coalition government, the policy that emerges is often the outcome of negotiations between governing parties. We argue that the credibility of exit threats by current coalition members and the importance of outside parties for the formation of potential alternative coalitions both matter for policy adoption. Building on a new data set measuring the expected coalition‐inclusion probabilities of parties in parlia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Consequently, the Green Party rose as an important plausible coalition partner of the Christian Democratic Union in the next election cycle, and the right-wing party began to consider tactics that could make the party more compatible as a future coalition partner for the Green Party. As a result, also as a response to the Fukushima nuclear disaster, Angela Merkel announced her plan to shut down eight nuclear reactors and completely phase out all the other reactors by 2022 (Kayser and Rehmert 2021).…”
Section: Party-competition Environmentsmentioning
confidence: 99%
“…Consequently, the Green Party rose as an important plausible coalition partner of the Christian Democratic Union in the next election cycle, and the right-wing party began to consider tactics that could make the party more compatible as a future coalition partner for the Green Party. As a result, also as a response to the Fukushima nuclear disaster, Angela Merkel announced her plan to shut down eight nuclear reactors and completely phase out all the other reactors by 2022 (Kayser and Rehmert 2021).…”
Section: Party-competition Environmentsmentioning
confidence: 99%
“…Yet, changes in public support for the individual coalition parties affect their bargaining power within the coalition (Lupia and Strøm 1995). This may increase the pressure to deviate from the coalition deal and may destabilize the current government (Kayser and Rehmert 2021; Lupia and Strøm 1995). Vice versa, a bad coalition mood might affect the relative strengths of the government parties in the polls, as the voters' responsibility attribution in coalition governments often differs across coalition partners (see, for example, Klüver and Spoon 2020).…”
Section: Concurrent Validitymentioning
confidence: 99%
“…The role of green parties as coalition partners is crucial, as it can vary from veto‐players to supporters (Evrard, 2012; Zohlnhöfer, 2003). Kayser and Rehmert (2020) showed that if green issues gain weight in public debate, this does not necessarily lead to a change. But if a green party is considered as a suitable coalition partner or becomes a coalition partner of another party, this increases the chance for policy change (Kayser & Rehmert, 2020).…”
Section: Analytical Approachmentioning
confidence: 99%